A Mixed-Methods Evaluation of the Feasibility of a Health Coaching Program to Improve Neuropathy Screening Practices and Prevent Foot Ulcers in Diabetic Patients at Risk of Complications - Pamungkas, Rian Adi; Chamroonsawasdi, Kanittha; Usman, Andi Mayasari (Jurnal Keperawatan Soedirman, 2025)
Neuropathy was crucial to develop foot ulcer complication. The study aimed to understand the needs and barriers to program implementation, assess feasibility, and examine the effects of diabetes health coaching programs on outcomes. This pilot study applied a sequential exploratory mixed-methods design that consisted of a quasi-Intervention design, pre-test, and post-test in the first phase, followed by a qualitative study in the second phase. Content analysis was applied to describe the qualitative findings. A paired t-test and independent t-test to measure mean differences within and between groups. The intervention group participated in a 12-week health coaching program including problem-solving coaching, narrative-based coaching, mindfulness coaching, skill coaching, and self-reporting. The keys findings were: 1) bridging the mind and body for consistency; 2) a heightened perception of susceptibility; 3) timing for being mindfulness; 4) inadequate knowledge and skills on diabetes complication; 5) a sense of embracement regarding diabetes complications. The quantitative study confirmed that patients who participated in the program showed significant improvements in knowledge, neuropathy screening, and foot ulcer prevention. Additionally, the program led to better clinical outcomes in preventing diabetic foot ulcer compared the control group. A health coaching program was feasible for implementation in the community health center.